RANCANG BANGUN POMPA HIDRAM UNTUK MENGATASI KETERBATASAN SUMBER ENERGI LISTRIK - Tauvana, Ade Irvan; Widodo, Widodo; Nulhakim, Lukman; Anugrah, Hari (P3M Politeknik Negeri Indramayu, 2025)
Puteran Village, Cikalong Wetan District, West Bandung Regency is the one that needs a hydram pump to utilize the spring water in Puteran Village to meet daily needs. This hydram pump is a pump that utilizes the power of water flowing from a source and some of the water is pumped to a higher place. This pump does not use electrical energy, so it can be used in areas where electricity is difficult or limited. This research includes design and assembly, this pump uses PVC pipe measuring ½